The role of government on women entrepreneurs and development: a study on the Joyeeta Foundation - Nezam, Nawshaba (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.